The Development of Learning Outcome-Based Islamic Education Materials to Improve The Students Critical Thinking - Karolina, Asri; Khodijah, Nyayu; Zuhdiyah, Zuhdiyah; Jamaluddin, Aini Syahira (Cendekia: Kependidikan dan Kemasyarakatan, 2022)
This study aims to develop learning outcome-based Islamic education materials in a module for the Islamic education department at IAIN Curup. This study employed a Research and Development method. The data were collected using questionnaires, interviews, observations, and documentation. The data were analyzed in both quantitative and qualitative ways. The analysis of quantitative data deployed percentage formulas, and the qualitative data analysis rested upon an interactive model comprised of data reduction, data display, and conclusion drawing. This study revealed that 89% of lecturers and 94.47% of students perceived that the existing Islamic education materials were less or not appropriate. In addition, all of them perceived those new materials were needed. The subsequent focused group discussion called for the urgency of developing learning outcome-based Islamic education materials in the form of a module. Such a module was further developed. The design consisted of three chapters titled the definition of Islamic Education and Sources of Islamic Education, Islamic Education Curriculum Itself, and Students. The module had 62 pages for the contents and 3 for the bibliography, totaling 65 pages. After being validated by four experts, the module was considered worthy, with a few revisions suggested. The learning outcome-based Islamic education materials are efficient based on the results of practicality tests on one-for-one evaluation (then the second revision) and small group evaluation. Students' critical thinking ability is included in the very high category of test results at intervals of 80-99.